AFTER PLANNING. - Yuengert, Andrew M. (First Things: A Monthly Journal of Religion & Public Life, 2017)
An essay is presented on thoughtful planning. Topics discussed include information about the book "Plans & Situated Actions" by Lucy Suchman on human action and communication; several guidance related to literature on planning and embodied skills such as acknowledgement of plans blindness and an importance of embodied skills in society changes.